Pustular Bazex Syndrome with Flexural Localization Associated with Metastatic Lung Carcinoma: Case Report - Cicek, Demet; Kandi, Basak; Demir, Betul; Dertlioglu, Selma Bakar; Cobanoglu, Bengu; Elkiran, Tamer (Ortadogu Ad Pres & Publ Co, 2011)
A 60-year-old male who had been diagnosed with metastatic lung carcinoma six years previously and had not accepted the a treatment was evaluated due to rash in his body. The patient's history revealed that the rash started six months ago on the back of the hand and extended to the upper extremities and his ear. Dermatological examination of the patient revealed erythematous-squamous plaques spread on flexural areas, bilateral upper limbs and ears, and pustules with peripheral location around the plaques. Histopathologically, there was hyperkeratosis, focal parakeratosis, small pustular change and perivascular lymphocytic infiltrate in the papillary dermis. Based on the clinical manifestation, presence of carcinoma and histopathologic evaluation, the patient was diagnosed as Bazex syndrome. In the present study, we have reported a very rare atypical form of Bazex syndrome due to psoriasiform lesions with acral and flexural location, accompanied by numerous pustules. This is the first case of acrokeratosis paraneoplastica in the literature that associated with metastatic lung carcinoma.
Keywords: Carcinoma, non-small-cell lung; paraneoplastic syndromes